Physical activity levels and energy expenditure of 9-year-old - 12-year-old overweight and obese children - Chanelle Kemp; Anita E. Pienaar (AOSIS, 2011)
The high occurrence of overweight and obesity amongst children is a disturbing health problem worldwide. Possible causes of increasing childhood obesity are inactivity and energy imbalances. The aim of this study was to analyse the total energy expenditure (TEE)and physical activity levels in 9-year-old - 12-year-old overweight and obese children during a weekday and a weekend day, as well as during a weekday morning and afternoon. Twenty-four 9-year-old - 12-year-old children (seven boys and 17 girls), of whom nine were overweight and 15 were obese, were selected from seven public primary schools for this study. Body mass index (BMI) cut-off points were used to distinguish between overweight and obese. Each participant wore an ACTICAL™ monitor to determine their physical activity levels and TEE. It was found that the TEE of the children did not differ between a week day and a weekend day, although the TEE of the week day afternoon differed significantly from that of the weekday morning. Unlike the overweight children, none of the obese children met the requirements of 60 minutes of moderate-intensity physical activity per day. Strategies should be found to increase the activity levels of overweight and, especially, obese children, specifically during the mornings and over weekends. Opsomming Die hoë voorkoms van oorgewig en obesiteit onder kinders is wêreldwyd 'n kommerwekkende gesondheidsprobleem. Fisieke onaktiwiteit en energiewanbalanse word as moontlike oorsake van die probleem beskou. Die doel van hierdie studie was om die totale energieverbruik (TEV) en fisieke-aktiwiteitsvlakke van 9-jarige - 12-jarige oorgewig- en obese kinders tydens 'n totale weeksdag en naweekdag te ontleed, asook tydens die oggend en middag van 'n weeksdag. Vier-en-twintig 9-jarige - 12-jarige kinders (sewe seuns en 17 dogters), waarvan nege oorgewig en 15 obees was, is uit sewe publieke laerskole vir die studie gekies. Afsnypunte volgens die liggaamsmassa-indeks (LMI) is gebruik om tussen oorgewig en obees te onderskei. Elke deelnemer het 'n ACTICAL™ monitor gedra om hul fisieke-aktiwiteitsvlakke en TEV te bepaal. Die studie het getoon dat die TEV van die kinders op 'n weeksdag en naweekdag nie verskil het nie, alhoewel TEV tydens die middag van die weeksdag betekenisvol verskil het van die oggend s'n. Anders as die oorgewig kinders, het geen van die obese kinders aan die voorgestelde riglyn van 60 minute se matig intensiewe fisieke aktiwiteit per dag voldoen nie. Strategieë moet gevind word om die vlakke van aktiwiteit van oorgewig en veral obese kinders te verhoog, spesifiek gedurende die oggende en oor naweke.